THE PHENOMENON OF VOWEL HARMONY IN THE TASHKENT DIALECT - Mirzayeva Guzal Qobuljonovna (Journals Park Publishing, 2025)
This article presents perspectives on the classification of Uzbek dialects, scholars’ views on dialects that preserve vowel harmony and insights into the phonetic characteristics of the Tashkent dialect, including how vowel harmony is maintained in this particular dialect.
Keywords: dialect classification, vowel harmony, ethnic groups, classification.